DESIGNING AND DEVELOPING PRODUCTS: IMPLEMENTATION OF BUSINESS-PROCESS AT THE INDUSTRIAL ENTERPRISE - Andrey P. Garnov; Svetlana P. Baurina (Вестник Российского экономического университета имени Г. В. Плеханова)
The article concretizes principle stages of the process of designing and developing products and shows key aspects, which should be focused on. The authors identify responsibilities and authorities in the business process being analyzed. They describe in detail the requirements and characteristics of in-coming and out-going data of the business process. The essence of activity dealing with analysis, verification and validation in managing the process of designing and developing products was presented. Implementation of the business process connected with designing and developing products is shown on the example of a big industrial enterprise of Russian machine-building, i.e. the Saransk machine-building works. The article enumerates shortcomings of organization of the process aimed at designing and developing products. Proposals dealing with the use of statistic methods of quality management were provided.